Structural, Optical and Thermal Properties of (PEG/PAA:MnO2) Nano Composites - Mohammed, Areej Ahmed; Ahmed, Adnan Raad; Al-Timimi, Muhammad Hameed (Technium BioChemMed, 2022)
In this work using manganese chloride and ammonia hydroxide in an aqueous solution as starting material to synthesize MnO2 nanoparticles by precipitation method The structural and optical and thermal properties of PEG PAA MnO2 Nano Composites films were investigated The PEG PAA polymeric blend films were doped with different ratios of MnO2 nanoparticles 0 1 3 and 5 using a casting method of 25 1 mm The obtained results demonstrated that the optical transmittance at the wavelengths between 200 1100 nm The optical properties of the films were affected by the MnO2 ratio The Energy gap of doped films decreased from 5 32 eV to 4 92 eV by increasing the doping MnO2 ratios The thermal conductivity coefficient K increases when adding MnO2 nanoparticles to the polymeric mixture PAA PEG.